2018
DOI: 10.1007/s00280-018-3690-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between folate concentration and expression of folate-associated genes in tissue and plasma after intraoperative administration of leucovorin in patients with colorectal cancer

Abstract: PurposeThe aim of study was to investigate the relationship between folate concentration and expression of folate-associated genes in tumour, mucosa and plasma of patients with colorectal cancer, after intraoperative administration of bolus leucovorin (LV).MethodsEighty patients were randomized into four groups to receive 0, 60, 200, or 500 mg/m2 LV, respectively. Tissue and plasma folate concentrations were assessed by LC–MS/MS. Gene expression of ABCC3/MRP3, FPGS, GGH, MTHFD1L, SLC46A1/PCFT, and SLC19A1/RFC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Wettergren in “The use of folate transporters as biomarkers in colorectal cancer therapy ” reported high expression of SLC46A1/PCFT, SLC19A1/RFC-1, and ABCC3/MRP3 was associated with longer 5-year disease-free survival (DFS) of patients with colorectal cancer ( n = 363) treated with adjuvant 5-fluorouracil plus leucovorin (FLV), whereas there was no association between expression and DFS in untreated patients [ 53 ]. Furthermore, a positive association between 3-year progression-free survival and ABCC3/MRP3 expression was found in patients with advanced colorectal cancer ( n = 294).…”
Section: Folate Receptors For Targeting Tumors and Inflammatory Diseamentioning
confidence: 99%
“…Wettergren in “The use of folate transporters as biomarkers in colorectal cancer therapy ” reported high expression of SLC46A1/PCFT, SLC19A1/RFC-1, and ABCC3/MRP3 was associated with longer 5-year disease-free survival (DFS) of patients with colorectal cancer ( n = 363) treated with adjuvant 5-fluorouracil plus leucovorin (FLV), whereas there was no association between expression and DFS in untreated patients [ 53 ]. Furthermore, a positive association between 3-year progression-free survival and ABCC3/MRP3 expression was found in patients with advanced colorectal cancer ( n = 294).…”
Section: Folate Receptors For Targeting Tumors and Inflammatory Diseamentioning
confidence: 99%
“…19 Cancer cells have increased demands of metabolic precursors; 20 thus, the possibility of targeting cancer cells by “feeding” them with DDSs loaded with specific precursors, represents a strategy for an effective perturbation of their evolution. 21–26…”
Section: Introductionmentioning
confidence: 99%
“…19 Cancer cells have increased demands of metabolic precursors; 20 thus, the possibility of targeting cancer cells by "feeding" them with DDSs loaded with specific precursors, represents a strategy for an effective perturbation of their evolution. [21][22][23][24][25][26] Since folate receptors are highly expressed in various human carcinomas such as: colorectal, heart, lung, kidney, ovarian, breast etc., 7 conjugating nanoparticles (NPs) with folic acid (e.g., gold NPs for cell imaging of nasopharyngeal malignancy 27 ) has proven to be a successful approach for targeting cancer cells for either visualization or drug delivery. [28][29][30][31][32][33][34] The expression level of folate receptors on the cell membrane is influenced by the cellular metabolism, the higher the proliferation rate (as it is naturally occurring in cancer cells), the more receptors are expressed compared to non-malign cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that there is a large interindividual difference in concentration of leucovorin in colorectal tumor tissue in response to a standardized dose of leucovorin [9]. This difference might be related to different expression levels of genes encoding influx and efflux folate transporters and of those involved in conversion of leucovorin to the active metabolite [6R]-MTHF [10][11][12]. Genderand age-associated pharmacokinetic differences have also been reported for folates and most oncologic drugs [13][14][15].…”
Section: Introductionmentioning
confidence: 99%